Kualitas Pelayanan Model CARTER Dan Pengaruhnya Terhadap Kepuasan Nasabah Bank Syariah Indonesia Kota Lhokseumawe Dengan Pendekatan SEM-PLS - Ahmad Fauzul Hakim (el-Amwal, 2023)
This study aims to determine the effect of service quality with the CARTER model on customer satisfaction at Bank Syariah Indonesia in the city of Lhokseumawe. The sampling technique used was purposive sampling technique. The number of samples is 100 people who are in the city of Lhokseumawe. The research data were analyzed using PLS-SEM (Partial Least Square – Structural Equation Modeling) with SmartPLS 3 software. The results showed that the service quality of compliance, assurance, reliability, tangibles, empathy, and responsiveness had a positive influence on customer satisfaction of Islamic Banks. Indonesia in the city of Lhokseumawe. Only two variables have a positive and significant effect, namely compliance and responsiveness variables, the remaining four variables, namely assurance, reliability, tangibles, and empathy, have a positive but not significant effect. The implication of this research is to focus on compliance, assurance, reliability, tangibles, empathy, and responsiveness that can affect customer satisfaction at Bank Syariah Indonesia in the city of Lhokseumawe. The results of this study have differences and similarities with previous studies. The difference with previous research is that it uses the measurement of service quality with the Servqual dimension and the similarity that both use the CARTER dimension.